2016
DOI: 10.5502/ijw.v6i3.526
|View full text |Cite
|
Sign up to set email alerts
|

The PERMA-Profiler: A brief multidimensional measure of flourishing

Abstract: In the book Flourish (2011), Seligman defined wellbeing in terms of five pillars: Positive emotion, Engagement, Relationships, Meaning, and Accomplishment, or PERMA. We developed the PERMA-Profiler as a brief measure of PERMA. We first compiled hundreds of theoretically relevant items. Three studies (N = 7,188) reduced, tested, and refined items, resulting in a final set of 15 questions (three items per PERMA domain). Eight additional filler items were added, which assess overall wellbeing, negative emotion, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

52
998
4
106

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 866 publications
(1,160 citation statements)
references
References 72 publications
52
998
4
106
Order By: Relevance
“…Integral measures that try to combine different wellbeing constructs include Ryff's Wellbeing Scales, which encompass six distinct dimensions of wellness (autonomy, environmental mastery, personal growth, positive relations with others, purpose in life, and selfacceptance) and have a range of versions, including 84-item, 54-item, and 18-item (Ryff & Keyes, 1995). The most recent measure tapping into the domains of Seligman's (2011) Wellbeing Theory is the PERMA Profiler -Short Form, a 15-item measure of positive emotion, engagement, positive relationships, meaning, and achievement (Butler & Kern, 2012).…”
Section: Measuring Eudaemonic Wellbeingmentioning
confidence: 99%
“…Integral measures that try to combine different wellbeing constructs include Ryff's Wellbeing Scales, which encompass six distinct dimensions of wellness (autonomy, environmental mastery, personal growth, positive relations with others, purpose in life, and selfacceptance) and have a range of versions, including 84-item, 54-item, and 18-item (Ryff & Keyes, 1995). The most recent measure tapping into the domains of Seligman's (2011) Wellbeing Theory is the PERMA Profiler -Short Form, a 15-item measure of positive emotion, engagement, positive relationships, meaning, and achievement (Butler & Kern, 2012).…”
Section: Measuring Eudaemonic Wellbeingmentioning
confidence: 99%
“…Since the Internet Paradox Study [16] found internet use to predict loneliness at follow-up, extensive literature has focused on the internet and loneliness specifically, but much less on general screen use, which indicates that this effect cannot be generalized to other screen types and warrants further investigation. This study aims to overcome gaps and limits in the previous literature firstly by using the PERMA-Profiler to focus on psychological flourishing instead of mental illness [32]; secondly by looking more specifically and more directly into positive relationships; and lastly by measuring the total hours per day of people's total screen use in an adult sample. Furthermore, as previous research has sometimes demonstrated gender differences for the PERMA-Profiler and UCLA Loneliness Scale used in the current study [32] [33], any gender differences will be controlled.…”
Section: Meaning (M) and Accomplishment (A) These Aspects Have Eachmentioning
confidence: 99%
“…This study aims to overcome gaps and limits in the previous literature firstly by using the PERMA-Profiler to focus on psychological flourishing instead of mental illness [32]; secondly by looking more specifically and more directly into positive relationships; and lastly by measuring the total hours per day of people's total screen use in an adult sample. Furthermore, as previous research has sometimes demonstrated gender differences for the PERMA-Profiler and UCLA Loneliness Scale used in the current study [32] [33], any gender differences will be controlled.…”
Section: Meaning (M) and Accomplishment (A) These Aspects Have Eachmentioning
confidence: 99%
“…This instrument was adapted to the work environment as the PERMA Workplace Profiler (Butler & Kern, 2016), including the previous 23 items adapted to the work place, of which four regard to negative aspects such as anger, anxiety, sadness and loneliness; and three remained the same, approaching general aspects not related to the work environment.…”
Section: Measurement Instruments For the Evaluation Of Occupational Mmentioning
confidence: 99%